(untitled) (Modern education and development, 2025)
Critical thinking is essential to effective learning and productive living. Since critical thinking can be defined in a number of different ways consistent with each other, we should not put a lot of weight on any one definition. Definitions are at best scaffolding for the mind. Critical thinking is thinking about humans thinking while they are thinking in order to make thinking better. Two things are crucial: critical thinking is not just thinking, but thinking which entails self-improvement; this improvement comes from skill in using standards by which one appropriately assesses thinking.